Circulating antibodies to cow's milk proteins in ulcerative colitis. - Jewell, D; Truelove, S (1972)
Sera from patients with ulcerative colitis (51), Crohn's disease (30), hypolactasia (13), untreated adult coeliac disease (11), irritable colon syndrome (24), and sera from 38 healthy control subjects were tested for antibodies to the principal cow's milk proteins-casein, alpha-lactalbumin, and beta-lactoglobulin. The red-cell-linked antigen-antiglobulin reaction was used to determine the titres of direct agglutinating antibodies and IgA and IgG incomplete antibodies. Apart from patients with coeliac disease, direct agglutinating antibodies were found infrequently and then in low titres. Approximately 50% of subjects had low titres of IgA and IgG antibodies. However, the titres found in sera from patients with ulcerative colitis did not differ from those found in the control subjects or in patients with Crohn's disease, hypolactasia, or irritable colon syndrome. Patients with untreated coeliac disease frequently had high antibody titres to the milk proteins. In all subjects tested, incomplete antibodies of IgA or IgG immunoglobulin class occurred with equal frequency. The frequent occurrence in adults of low titres of antibodies to the milk proteins may be due to continued absorption of minute amounts of protein. Absorption of allergens may be facilitated by mucosal damage, such as that of coeliac disease, with stimulation of antibody production. At the present time, however, there is little evidence to suggest that milk allergy is a factor in the aetiology of ulcerative colitis.